Descriptions of a new species and of three unknown males of Xylocopa Latreille, 1802 from the Neotropical region (Hymenoptera: Apidae: Xylocopini) - Zama, Paula C.; Silveira, Fernando A. (Zootaxa, 2024)
A new species of the previously monotypic subgenus Xylocopa (Xylocopina), X. asedothae Zama & Silveira sp. nov., and males of three species previously known only from females, X. (Diaxylocopa) truxali Hurd & Moure, 1963, X. (Dasyxylocopa) fortuita Melo, 2017 and X. (Schonnherria) ornata Smith, 1874, are described and illustrated for the first time. Diagnoses, comments on morphological variation, photographs and updated geographical distributions for all them are also provided. An identification key for both sexes of the species of X. (Dasyxylocopa) is updated and photographs of the genital capsules for males specimens used here are also provided.